Analysis of the Influence of Digitalization on MSME Productivity in Southeast Asia: An Econometric Data Panel TApproach - Lestari, Ayu; Anggraeni, Riska (Journal of Applied Econometric, 2025)
This study aims to analyze the impact of digitalization on the productivity of Micro, Small, and Medium Enterprises (MSMEs) in Southeast Asia, with a focus on three countries: Indonesia, Thailand, and Vietnam. Using a qualitative approach, data were collected through interviews with MSME owners and managers, questionnaires distributed to employees, and direct observation at MSME locations. The study's results show that digitalization, through the use of e-commerce platforms, digital payment systems, and technology based inventory management, significantly contributes to improving operational efficiency and market access for MSMEs. However, the main challenges faced are low digital literacy and limited infrastructure, particularly in rural areas, which hinder MSMEs' ability to leverage digital technology fully. In countries with better digital infrastructure, such as Thailand, the positive impact of digitalization is more pronounced. This research suggests the need to enhance digital literacy training and improve infrastructure to support the adoption of technology by MSMEs. These findings offer valuable insights for developing MSME policies in Southeast Asia that can enhance competitiveness in the global market.